Commercial diplomacy in the service helping to attract foreign direct investment - Bellina, Željko (Teorija in praksa, 2019)
In this paper, the example of the Republic of Serbia is considered to show that commercial diplomacy can be a useful foreign policy instrument by helping to attract foreign direct investment from emerging countries (many of which Serbia enjoys good political and/or close cultural relations with), that are widely regarded as the drivers of global economic growth in the future. The Russian Federation and the People's Republic of China are viewed as the target countries. Given that many emerging countries have fast-growing economies and are increasingly investing abroad, the presented data allow us to conclude that not only Serbia, but other Western Balkans countries too, as well as transition and/or developing countries generally need to strengthen their commercial diplomacy towards the emerging countries in order to attract as much foreign direct investment as possible to boost their economic development, growth and employment.
Keywords: Diplomacija; Diplomacy; Economy; Foreign investments; gospodarska diplomacija; Gospodarstvo; Transition; Tranzicija; Tuje naložbe